Investigating the GWAS-Implicated Loci for Rheumatoid Arthritis in the Pakistani Population. (3rd August 2020) - Aslam, Muhammad Muaaz; John, Peter; Fan, Kang-Hsien; Bhatti, Attya; Aziz, Wajahat; Ahmed, Bashir; Feingold, Eleanor; Demirci, F. Yesim; Kamboh, M. Ilyas
Abstract : Rheumatoid arthritis (RA) is a complex and multifactorial autoimmune disorder with the involvement of multiple genetic and environmental factors. Genome-wide association studies (GWAS) have identified more than 50 RA genetic loci in European populations. Given the anticipated overlap of RA-relevant genes and pathways across different ethnic groups, we sought to replicate 58 GWAS-implicated SNPs reported in Europeans in Pakistani subjects. 1, 959 unrelated subjects comprising 1, 222 RA cases and 737 controls were collected from three rheumatology facilities in Pakistan. Genotyping was performed using iPLEX or TaqMan® methods. A total of 50 SNPs were included in the final association analysis after excluding those that failed assay design/run or postrun QC analysis. Fourteen SNPs ( LINC00824 /rs1516971, PADI4 /rs2240336, CEP57 /rs4409785, CTLA4 /rs3087243, STAT4 /rs13426947, HLA-B/MICA /rs2596565, C5orf30 /rs26232, CCL21 /rs951005, GATA3 /rs2275806, VPS37C /rs595158, HLA-DRB1 /rs660895, EOMES /rs3806624, SPRED2 /rs934734, and RUNX1 /rs9979383) were replicated in our Pakistani sample at false discovery rate (FDR) of <0.20 with nominal p values ranging from 4.73 E -06 to 3.48 E -02. Our results indicate that several RA susceptibility loci are shared between Pakistani and European populations, supporting the role of common genes/pathways.